SINTESIS MEMBRAN POLIURETAN BERBASIS MINYAK BIJI ALPUKAT (Avocado Seed Oil) DAN HEKSAMETILEN-1,6-DIISOSIANAT (HMDI) - Fitriani Fitriani; Marlina Marlina; Khairan Khairan (Jurnal Natural, 2016)
This research aims to synthesize polyurethane membrace from avocado seed oil as a source of hydrixyl (-OH) and hexametylhene -1.6-dissocyanate (HDMI) as a source of isocynate (-NCO). The oil were extracted from avocado seeds at temperature of  60-80oC for 2 hours using n-hexane solvent. The results of FTIR spectrum analysis from avocado seed oil showed that there were -OH clusters absorption on the wavelength number of 3393.819 cm-1, thus this oil can be used to synthesize polyurethane membrane. The isocyanate composition, time and temperature during synthesis process of polyurethane membrane were varied. The polyurethane membrane were moulded in petri dishes, then heated up for 48 hours on the temperature of  70oC, and finally taken out from its mould. The characteristics of the polyurethane membrane from avocado seed oil are brown in colour, homogenous, elastic, solid, transparent and shaped like a membrane. The measurements from FTIR spectrum showed that the -NCO clusters are no longer present. This condition happened because there were no more absorption in the wavelength number of  2270 cm-1 . It can be concluded that the isocyanate has completely reacted during polymerization and the curing process, thus urethane was created in the 1699,965 cm-1 absorption which was the urethane C=O clusters absorption.